Major depression and dimensional representations of DSM-IV personality disorders: a population-based twin study - Reichborn-Kjennerud, T. (2009)
BACKGROUND: Major depressive disorder (MDD) co-occurs frequently with personality disorders (PDs). The extent to which this results from shared genetic or environmental risk factors remains uncertain. METHOD: Young adult twins (n=2801) from the population-based Norwegian Institute of Public Health Twin Panel were assessed at personal interview for DSM-IV lifetime MDD and the 10 Axis II PDs. The relationship between MDD and dimensional representations of all PDs was explored by stepwise logistic regression. Multivariate Cholesky twin models were fitted using the Mx program, and genetic and environmental correlations were estimated. RESULTS: Dimensional representations of borderline (BPD), avoidant (AVPD) and paranoid personality disorder (PPD) were independently and significantly associated with increased risk for MDD. Multivariate twin modeling indicated that one latent factor accounted for the genetic covariance between MDD and the three PDs. The genetic correlations between MDD and dimensional representations of BPD, AVPD and PPD were +0.56, +0.22 and +0.40 respectively. No sex differences or shared environmental effects were found. The structure of the individual-specific environmental factors influencing MDD and the three PDs were similar to the genetic factors but the environmental correlations were lower: +0.39, +0.23 and +0.27 respectively. CONCLUSIONS: There is substantial overlap between liability factors for MDD and BPD from cluster B, PPD from cluster A and AVPD from cluster C. The vulnerability to general PD pathology and MDD seem to be closely related. The patterns of co-morbidity observed between diverse psychiatric disorders might result from just a few liability factors.